Freedom and Political Order in Late Medieval Castilian Towns (Edad Media. Revista de Historia, 2020)
This article analyses the relationship between the codes of freedom and the political order in the late medieval Castilian towns up to the War of the Communities. It is argued that, although the political language of freedom comes at a late stage, the analysis of the procedures and the language of the popular protest reveals the existence of what can be called a paradigm of freedom in the city. This was linked to the collective construction of the city as a political body with a series of shared assumptions about its own government. The last section of the article analyses the institutional changes in the cities during the War of the Communities to show their connections with this paradigm of freedom and with the institutions that represented the urban political body.
Keywords: Freedom; Cities; Political-Culture; revolts; Castile; Late Middle Ages; War of the Communities of Castile